Loss Minimization and Allocation of Unbalanced Radial Distribution Network - Kaur, Manvir (My University, 2018)
In this thesis it has been tried to discover the possibilities of loss minimization in unbalanced radial electrical power distribution networks. It has been found that the losses can be minimized by two main methods, which are network reconfiguration and optimal placement of DG and capacitor. To apply these remedial steps on the distribution networks an efficient load-flow solution method for three-phase unbalanced radial distribution network has been proposed so that the actual condition related to node voltage and its angle, branch current, real power loss, reactive power loss, branch losses etc. of the network can be computed. Simple equations are used to relate the sending-end voltage, receiving-end voltage and voltage drops in each branch of the distribution system. An algorithm is developed to find out the respective parameters. The angle of the receiving-end voltage is also computed along with the magnitude of the voltage. It is an iterative method. The flat voltage (1p.u.) start from substation to every end-node is considered. The voltage magnitude and angle are updated after each successive iteration and the voltage drops are then computed by using the new obtained values of voltage magnitude and angle. The proposed method has been implemented on 19-node and 25-node unbalanced distribution networks. The comparison of speed requirement by the proposed method with the other recent method has been verified to show its efficiency. In power distribution network losses occurring in the network are one of the important components, and effort should be done to reduce their value. There exist different approaches for loss minimization and most important one is, reduction of distribution network losses by network reconfiguration. In the present work 19-node and 25-node unbalanced distribution networks have been considered for loss reduction. Fuzzy –firefly algorithm is applied to find out the optimal configuration of the system with minimum losses, giving the status of opened and closed switches. This approach is applied on both the test systems and the results are recorded and compared with the other techniques found in literature work. The voltage profile of distribution network has been improved by reducing the reactive component of power by optimal capacitor placement and for the reduction of active power loss, DG has also been allocated in the reconfigured network. The sizes of DG and capacitor are computed by utilizing Bacteria foraging optimization algorithm (BFOA). Results are also compared for real power loss, reactive power loss and minimum voltage for before and after integration of DG and capacitor. The results obtained are effective and DG and capacitor placement for loss minimization along with reconfiguration comes out to be a decent choice. Nowadays, the classic model of functioning of regulated electricity market is being replaced by the newly formed deregulated energy market, where generation, transmission and distribution comes out as single independent entities. The main burden in this market comes in the form to maintain low-cost electricity, efficient capacity expansion planning, and better service. So here reconfiguration of 25-node unbalanced distribution network is also done in deregulated environment taking minimization of operating cost and reliability optimization as main components of objective function. The optimal reconfigured network of 25-node unbalanced radial distribution network in deregulated environment is found by the firefly algorithm. DG and capacitor are placed in reconfigured network for further loss reduction and results are compared and found to be effective. After reducing the distribution network losses, the important part is to allocate the losses to different system entities, so that we can find the contribution of each and every important component towards network losses. Loss allocation basically refers to the expenditures linked with losses to distinct customers of the distribution network. In the present work the loss allocation of unbalanced radial distribution network has been carried out by using fuzzy-firefly algorithm. Also, a loss allocation method by integrating of DG and Capacitor in the reconfigured network is formulated. The loss allocation in unbalanced distribution networks in both the regulated and deregulated environments are presented for 25-node unbalanced distribution networks for before and after network reconfiguration and also after integration of DG and capacitor in the reconfigured network. Also, loss allocation is performed for IEEE 13-node test feeder and the results obtained by the proposed method and method available in literature are compared and the proposed method gives the loss allocation in more uniform way as compared to existing technique.
Ph.D. THESIS
Keywords: Unbalanced; Radial distribution network; DG placement; Reconfiguration; Load-flow